2022
DOI: 10.3389/fnagi.2022.894824
|View full text |Cite
|
Sign up to set email alerts
|

REPS1 as a Potential Biomarker in Alzheimer’s Disease and Vascular Dementia

Abstract: Vascular dementia (VD) and Alzheimer’s disease (AD) are common types of dementia for which no curative therapies are known. In this study, we identified hub genes associated with AD and VD in order to explore new potential therapeutic targets. Genes differentially expressed in VD and AD in all three datasets (GSE122063, GSE132903, and GSE5281) were identified and used to construct a protein–protein interaction network. We identified 10 modules containing 427 module genes in AD and VD. Module genes showing an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 53 publications
0
17
0
Order By: Relevance
“…Previously, studies have identified molecular signatures of blood cell origin and potential therapeutic targets through a comprehensive analysis of AD-related datasets [44]. Some studies have also analyzed brain tissue samples from AD patients by bioinformatics to look for biomarkers of AD [45][46][47]. Another study was used a web-based approach to identify biomarkers and therapeutic agents for AD [48].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, studies have identified molecular signatures of blood cell origin and potential therapeutic targets through a comprehensive analysis of AD-related datasets [44]. Some studies have also analyzed brain tissue samples from AD patients by bioinformatics to look for biomarkers of AD [45][46][47]. Another study was used a web-based approach to identify biomarkers and therapeutic agents for AD [48].…”
Section: Discussionmentioning
confidence: 99%
“…A hallmark of the early phase of AD is vessel impairment [ 2 ]. AD and VCDs coexist and share similar biomarkers [ 3 ], indicating the importance of investigating their mechanisms and identifying treatments for these two types of dementia. In fact, memory impairment is thought to be the core feature of CI, and the mechanisms underlying different processes of memory have attracted much attention in this regard.…”
Section: Introductionmentioning
confidence: 99%
“…A study identified significant marker genes, which could be related to a potential AD molecular type ( 20 ). Studies have shown that REPS1 serves as a potential biomarker for AD and Vascular dementia that were both associated with Ras signaling ( 21 ). Furthermore, lncRNAs and miRNAs determining the progression of AD, including miR-34a ( 22 ) and long ncRNA MALAT1 ( 23 ).…”
Section: Introductionmentioning
confidence: 99%